2021
DOI: 10.1080/26415275.2021.1906879
|View full text |Cite
|
Sign up to set email alerts
|

The effect of refractive index of fillers and polymer matrix on translucency and color matching of dental resin composite

Abstract: Objective When restorative resin composites absorb light from the surrounding tooth structures, it creates a color-match, which is known as ‘a chameleon effect’. In this study, series of co-monomer mixtures were prepared with an increasing refraction index (RI) and mixed with glass fillers. The aim of this study was to optimize the mismatch of RI of resin/fillers to create the chameleon effect. Materials and Methods BisGMA/TEGDMA resins were prepared with seven differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 20 publications
2
43
0
3
Order By: Relevance
“…The results showed that the additives slightly reduced the DC of the experimental materials due probably to the mismatch between the refractive index (RI) of fillers and monomers. The RI of fillers was expected to fall within 1.4–1.5 [ 55 ] to match with the RI of the monomer mixture such as UDMA/TEGDMA (RI~1.45) [ 10 ]. Although the actual refractive indices of MCPM and Sr/F-BGNPs are not known, the result indicated that the effect of the additives on the reduction of DC upon light activation was minimal (~2%) compared to that reported in the previous studies (~4–10%) [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the additives slightly reduced the DC of the experimental materials due probably to the mismatch between the refractive index (RI) of fillers and monomers. The RI of fillers was expected to fall within 1.4–1.5 [ 55 ] to match with the RI of the monomer mixture such as UDMA/TEGDMA (RI~1.45) [ 10 ]. Although the actual refractive indices of MCPM and Sr/F-BGNPs are not known, the result indicated that the effect of the additives on the reduction of DC upon light activation was minimal (~2%) compared to that reported in the previous studies (~4–10%) [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main goals of aesthetic restorative dentistry is to develop a restoration that matches the optical qualities of the natural tooth. The current trend of reducing clinical restorative treatment time and simplifying color matching has promoted dental manufacturers to compete to develop a universal resin composite (single shade) that might potentially match a wide variety of classic shades (Oivanen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Translucency is an optical property that lies between opacity and transparency in terms of the amount of light that can pass through a material. Unlike transparent materials, translucent materials scatter light rays and prevent objects behind the material from being seen clearly [ 4 ]. The translucency parameter (TP) is used to assess the translucency of restorative materials.…”
Section: Introductionmentioning
confidence: 99%